Tinjauan Hukum Islam terhadap Ketentuan Penegakan Hukum Pemberantasan Korupsi di Indonesia - Iswandi, Iswandi; Bukhari, Bukhari (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study seeks to find solutions to the rampant corruption practices in Indonesia today. The purpose of this study is to further reason about the legal norms contained in the legislation related to law enforcement corruption eradication in Indonesia by using the approach of Islamic law theory. The research method used in this study is a normative juridical approach that is done by examining the theories, concepts, principles of law, legislation by putting the law as a building system of legal norms. the results of the study conducted that the legal norms contained in the legislation on the eradication of corruption contains only two elements, namely AR-Rashi and al-murtashi, on the contrary in Islamic law there are three elements of ar-Rashi, al-murtashi and ar-Ra'isy. If the element of ar-raisy (intermediary) is not absorbed into the sub-system of Corruption Eradication law, it will become very weak. the concept of punishment in the Corruption Eradication legislation is limited to imprisonment and fines, while in Islamic law it is divided into three categories, namely; First, the ta'zīr law which is about the body consisting of the death penalty and volumes; second, the ta'zīr punishment which is about the independence or freedom of a person in the form of imprisonment; and Third, ta'zīr law regarding property, such as punitive damages or fines and confiscation so that Islamic law looks more comprehensive and systematic.